Price Discrimination in the Airline Industry - Stringer, Elizabeth (2008)
In the past 10 to 15 years we have seen the emergence of low cost, "no frills" airlines competing directly with traditional carriers. This increase in competition coupled with the growing use of the internet has significantly increased price transparency within the airline industry. The primary aim of this study is to determine if and how price transparency has altered the way airlines price discriminate.